Oral health care of people with Angelman syndrome in Germany – a questionnaire-based study - Peter Schmidt; Caroline Tantzen; Oliver Fricke; Andreas Gerhard Schulte (BMC Oral Health, 2025)
Abstract Background Caregivers of people with Angelman syndrome (AS) in Germany were surveyed to amend a lack of information on supportive and preventive oral care for persons in this group. Methods Returned anonymized questionnaires that had been sent to the approx. 600 members of the German Angelman Syndrome Association were evaluated. The study was approved by the ethics committee of Witten/Herdecke University (# 121/2021). Results In total, 220 questionnaires for people with AS aged between 1 and 54 years old (mean age 17.0 years) were evaluated. Overall, 38.1% (n = 84) of the people with AS were younger than three years at their first dental appointment; 60.0% (n = 132) tooth brushed twice daily; 15.9% (n = 35) brushed for 2–3 min; and 78.5% (n = 172) did not use dental hygiene products other than toothbrushes. Age-specific differences emerged: Although only 45.0% (n = 45) of people with AS ≥ 18 years (n = 100) began tooth brushing in the first year of life, this increased to 69.7% (n = 89) for people with AS < 18 years (n = 119). Also, while 76.5% (n = 91) of people with AS < 18 years were usually assisted with tooth brushing by the same person, this applied to only 50.0% (n = 50) of people with AS ≥ 18 years (p < 0.001; Chi-Square-Test). Conclusions There are age-dependent differences in tooth brushing behavior among people with AS. Irrespective of age and sex, nearly all people with AS required life-long oral health support at home. Professional oral health support, e.g., regular check-ups, individual prophylactic measures, and dental cleaning, remains essential for this group. Hence, efforts must be increased to develop and offer more interprofessional dental prophylaxis concepts for people with AS of all ages, from infancy to senescence. These findings accord with those for other groups of people with syndromic disorders, such as Down syndrome. Clinical trial number Not applicable.